LIFE STYLE INDICATORS OF INDUSTRY WORKERS IN SANTA CATARINA IN THE SESI GINÁSTICA NA EMPRESA PROGRAM (Fiep Bulletin - online, 2012)
The objective of this study was to verify some indicators of lifestyle and Practice of Physical Activity in Leisure, Individual Health Perception, Perception of Stress and smoking of workers in companies served by SESIGE in Santa Catarina, in order to become a reference to used in future research. This survey was conducted in 2011, through research proposals in 2010, which applied to employees of companies assisted by the Program SESIGE Santa Catarina. It is a descriptive and quantitative. Processing, data processing and statistical analysis were performed using the Sphinx software version 5.1.0.5. Data analysis considered the number of citations and we used univariate and bivariate statistics. To evaluate the association between two variables used the chi-square adopting the statistical significance level of 99.9% (p
Keywords: Indicators of lifestyle; Professional; Labor Gymnastics